The Effect of Corruption on International Trade: A Case Study of Indonesian Trade to Nine Countries - Danang Ibnu Atsir; Sunaryati Sunaryati (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2018)
Corruption is a form of abuse of ethical authority by public officials, which is divided into two parts: bribery and forced collection. The effect of corruption like bribes and illegal levies is widespread in the public sector. One interesting investigation is the effect of corruption on international trade. Corruption becomes a barrier in international trade, where corruption plays a role in the access of trade goods and services from within and abroad. Using the gravity model, the focus of this research was the effect of corruption on international trade by taking a case study of Indonesia’s bilateral trade with its nine largest export destination countries. Using panel data, analysis tools used in this research were common effect, fixed effect, random effect and poisson pseudo maximum likelihood (PPML). In this research, it was found that geographical distance variable in its fixed units caused the omitted variable so that the error term correlated with independent variables. In order to overcome the problem, poisson pseudo maximum likelihood method was used in performing regression gravity model with linear log form, so the omitted variable issue on the geographical distance can be eliminated. The results of this research concluded that corruption played a role in international trade through bureaucratic mechanisms of trade and investment licensing and the effect of corruption was more detrimental to exporters.Keywords: Gravity Model, Corruption, International Trade, Poisson Pseudo Maximum Likelihood (PPML).